Harmonising School Leadership And Foundations For Human Resource Development In Early Childhood Education - Ahmad Nur Ismail; Deriana Febrianti; Umi Kasanah; Heru Setiawan; Edy Suprayitno (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to identify research gaps in the harmonisation of school leadership and foundations in the development of human resources (HR) within Early Childhood Education (ECE) institutions. Although several studies address the relationship between leadership and HR development, research specifically examining the dynamics between school leadership and foundations in the context of ECE remains limited. Employing a qualitative case study approach, data collection techniques include in-depth observations, and interviews. The data obtained is analysed through data reduction, presentation, and conclusion drawing. The findings indicate that the educator standards at TKIT Nurussyifa encompass four key competencies: pedagogical, social, personal, and professional. Each teacher is expected to possess these competencies to effectively fulfil their responsibilities. The headteacher’s role is to lead and guide teachers in school activities and programmes, while teachers are accountable for the learning process. The foundation plays a crucial role in supporting the headteacher and teachers, as well as managing the school’s operational funding. In terms of management and HR development, the foundation seeks to enhance teaching quality through selective and intensive teacher recruitment. The headteacher also actively contributes to the professional development of teachers through relevant seminars and training. The practical implications of this study suggest that school and foundation managers must continue to collaborate to create an environment conducive to the development of quality human resources. Consequently, this harmonisation benefits not only the educational institution but also positively impacts students and the broader community.